Pemberdayaan Ruang Praktik Kelistrikan SMK Bina Mandiri Sejahtera dan Penggunaan Modul Sistem Pengereman Motor Listrik - Anggi Mardiono; B. S. Rahayu Purwanti; Ihsan Auditia Akhinov; Endang Saefudin; Hasvienda Mohammad Ridlwan; Safitri Latifah (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2026)
This article discusses the implementation of student practice space optimization in Community Service (PkM) activities at SMK Bina Mandiri Sejahtera (BMS). The limited procurement facilities carried out at SMK BMS require a solution and the PkM-LK Team has designed an automotive electrical system practice module to develop insights into non-conventional braking. Updates to the mechanical and electrical modules designed in 2022. Namely the Regenerative Braking system to Dynamic and Static on BLDC motors. The purpose of PkM-LK is to increase the insight of teachers and students into electric motor braking systems, and to complete practical learning facilities for Light Vehicle Engineering students, SMK BMS Citeureup. Increased insight is provided through discussions and observations of the use of modules by students together with PNJ students under the supervision of the PkM Implementing Lecturer involving Industrial Electronics students has been completed with the realization of practical tools/modules that can be used independently by all TKR students, the teaching teachers. One by one students practice using dynamic, static, and regenerative braking modules. All students were divided into three groups, each with 24 students as practicum participants, led by two students and assisted by three junior students. Teachers also contributed to discussions with lecturers and under the guidance of the Head of Study Program. This demonstrates the success of the PkM-LK activity as a contribution to empowering the use of the Electric Motor Braking System practice module at SMK BMS.